PENGARUH PEMBIAYAAN MURABAHAH TERHADAP ROA (RETURN ON ASSET) ( Studi Kasus Pada Tiga Bank Umum Syariah Di Indonesia Periode 2017-2019) - Ekawati, Meta; Fadjar, Mumu M.; Karini, Tina (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study aims to determine the effect of murabaha financing on ROA (Return On Assets). The variables used in this study are murabaha financing, and ROA (Return On Assets). This research was conducted using quantitative methods with an associative approach. The population in this study is the financial statements of the Sharia Commercial Banks in the 2017-2019 period as many as Three Sharia Commercial Banks and 36 financial statement samples are taken. In this study sampling the sample with a purposive sampling technique. Data collection techniques using secondary data. Data analysis techniques used are the classic assumption test, multiple linear analysis, and hypothesis testing. The results of this study indicate: the independent variable is murabaha financing while the dependent variable is ROA (Return On Asset). The results of this study indicate that partially murabaha financing has an effect on ROA (Return On Assets) with t test results of 2.555 with a significant value of 0.015. It can be concluded that murabaha financing has an effect of 16.1% on ROA (Return On Assets) and the remaining 83.9% is influenced by other factors not examined in this study.